EVALUASI PEMETAAN WILAYAH DESA DAWUNGSARI DENGAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS (SIG) - Fatimah, Dini Destiani Siti; Muhtadin, Fauzan Azmi; R, Alvarizky Putra Kurniawan; Febrian, Rivan; Husaeni, Fachri Ahmad Al; Saputra, Muhamad Dzaki; Maridjan, Maula Muhammad; Fitriyani, Dila; Mustofa, Muhamad Zaenal; Diniyaturobiah, Hanipah; Muzaky, Rifky Khoerul; Resita, Rasty; Mujahid, Wildan; Mulyana, Abdurrahman; Rafiqi, Putri Aufa; Maulana, Rifki Ilham; Noviansyah, Ikhwan; Adawiyah, Alya; Khaerurijal, Fajar; Baasith, Azry Abdul; Ardhillah, Zian Zaky (Institut Teknologi Garut, 2025)
Amidst the rapid development of urbanization and increasing population, the challenges in regional planning and management are increasingly complex, especially in rural areas such as Dawungsari Village. This study aims to map the distribution of small businesses and public facilities, such as places of worship, sports facilities, educational facilities, and other village infrastructure. Data were collected through direct observation and local sources, then visualized in the form of a regional map. This mapping provides a comprehensive representation of the distribution of public facilities and services in the village, and provides a basis for supporting more effective development planning. The evaluation shows that the mapping method used is able to produce relevant information for regional management, although there are constraints related to data accuracy and limited local resources.